Typewriting Mass Observation Online: Media Imprints on the Digital Archive. (19th February 2019) - Wright, Rebecca K
Abstract: This article examines how the digital is politicizing medium within historical studies. Through a critical evaluation of Mass Observation Online (MOO: the online portal for the Mass Observation Archive), the paper traces how OCR (Optical Character Recognition) has established a new hierarchy in a key archive of British social memory, centred around the typewriter, whose products can be transformed into searchable digital text. It shows how a new economy of representation has been created based not on what Observers wrote, but what they wrote with. This has serious historiographical consequences for research drawn from MOO. Typewriting during the interwar period was connected to wider historical forces, including changes in white-collar work, gender roles and cultures of representation. Privileging typewritten material, therefore, is changing how we understand MO materials: from the constitution of the national panel, to the identity of Observers, the form and content of materials, and the nature of life-writing. This distortion is not limited to MOO, but this article will show how the digital has made medium a key site around which primary source materials, archival collections and digital interfaces are being structured. As historical collections are increasingly accessed through digital interfaces, it is argued that increased attention must be paid by historians and archivists to the historiographical dimensions of media and its impact on digital historical collections.